The thermodynamics of template-directed DNA synthesis: Base insertion and extension enthalpies - Minetti, Conceição A. S. A. (National Academy of Sciences, 2003)
We used stopped-flow calorimetry to measure the overall enthalpy change associated with template-directed nucleotide insertion and DNA extension. Specifically, we used families of hairpin self-priming templates in conjunction with an exonuclease-free DNA polymerase to study primer extension by one or more dA or dT residues. Our results reveal exothermic heats between –9.8 and –16.0 kcal/bp for template-directed enzymatic polymerization. These extension enthalpies depend on the identity of the inserting base, the primer terminus, and/or the preceding base. Despite the complexity of the overall process, the sign, magnitude, and sequence dependence of these insertion and extension enthalpies are consistent with nearest-neighbor data derived from DNA melting studies. We recognize that the overall process studied here involves contributions from a multitude of events, including dNTP to dNMP hydrolysis, phosphodiester bond formation, and enzyme conformational changes. It is therefore noteworthy that the overall enthalpic driving force per base pair is of a magnitude similar to that expected for addition of one base pair or base stack per insertion event, rather than that associated with the rupture and/or formation of covalent bonds, as occurs during this catalytic process. Our data suggest a constant sequence-independent background of compensating enthalpic contributions to the overall process of DNA synthesis, with discrimination expressed by differences in noncovalent interactions at the template–primer level. Such enthalpic discrimination underscores a model in which complex biological events are regulated by relatively modest energy balances involving weak interactions, thereby allowing subtle mechanisms of regulation.